2022
DOI: 10.1177/23247096221090840
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Thyroidal Coccidioidal Infection

Abstract: Infection of the thyroid gland with Coccidioides immitis is rare. We report a case with disseminated coccidiomycosis involving thyroid gland as a thyroid nodule. Although historical autopsy studies have indicated that coccidioidal involvement of the thyroid gland can infrequently occur as part of disseminated infection, to our knowledge, only less than 10 other cases have been reported. Optimal treatment duration and dosage of medication are uncertain in literature of this rare involvement of thyroid gland wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Some recommend high-dose daily uconazole (600-800 mg daily based on tolerance) for up to 36 months of treatment. Other studies support using isavuconazonium as the most effective and least toxic azole in refractory patients (4). Also, some patients required surgery for adjunctive or de nitive treatment.…”
Section: Discussion Include a Very Brief Review Of Similar Published ...mentioning
confidence: 99%
“…Some recommend high-dose daily uconazole (600-800 mg daily based on tolerance) for up to 36 months of treatment. Other studies support using isavuconazonium as the most effective and least toxic azole in refractory patients (4). Also, some patients required surgery for adjunctive or de nitive treatment.…”
Section: Discussion Include a Very Brief Review Of Similar Published ...mentioning
confidence: 99%
“…Their literature review of just five cases revealed instances of tongue infection. In a related study, Raza et al discussed an unusual case of disseminated Coccidioidomycosis in a thyroid nodule (4). They pointed out the rarity of thyroid involvement, with fewer than 10 cases reported.…”
Section: Discussionmentioning
confidence: 99%